Website-Based E-Library Of The Yellow Book - Billah, Mohammad Manazil; Airlangga, Primaadi; Zainul Arifin, Muhyiddin; Yaqin, Nurul (SAINTEKBU, 2022)
The yellow book is one of several media for learning about good Islamic religious knowledge and needs to be studied by Muslims. However, only Islamic boarding school students can study the book. This is due to the difficulty in learning it independently, especially for ordinary people who lack or have not mastered Arabic. Besides that, the book is only available in the form of a book that is easily damaged and difficult to carry anywhere. From this subject, this research focuses on making a web-based book library application with Indonesian translation. The method used is Waterfall. This method has the analysis stage: an observation of the existing system. The design stage: making a flowchart and DFD design, the coding stage, and the testing stage. The results obtained are the web-based Yellow Book library application that can make it easier for Muslims to study the Yellow Book daily because this application has access to material in the form of the Yellow Book along with the audiobook in Arabic and a video link for studying the yellow book.